(3adSaI GdJWhQ ai GdacQ GdGfSGfi h JbfjGJ GdMGSH GdGdi ai GdYeGQI GdPcjI h GKQgG Ydi GdJUeje GdOGNdi (B=s philosophy transformation of human thought and computer technology in smart architecture and its impact on interior design - (3LjgGf GHQGgje GMeO GdOLhis; (3SYjO MSf YHO GdQMefs; (3TQja MSjf MSfis; (3LGeYI MdhGf(B.s (3cdjI Gdafhf GdJWHjbjI(B.s (3bSe GdJUeje GdOGNdi h GdGKGKs ((3LGeYI MdhGf ;s (3cdjI Gdafhf GdJWHjbjI(B. (3bSe GdJUeje GdUfGYj(B.s, 2016)
(3hef GdGgOGa (B:(3JJHY h JMdjd adSaI GdJMhd GdacQi GdhGbY ai GdYeGQI h GfYcGSg Ydi GdJUeje GdOGNdi h GJLGgGJg GfJbGdG ef GHLOjGJ GdbQf GdYTQjf Gdi GdbQf Gd(B21 (3ai Xd GdJMhd ef JGKjQGJ GdacQ GdGfSGfi Gdi JWHjbGJ GdMGSH GdGdi(B.(3GdefgL GdeSJNOe(B:(3GdJGQjNI GdJMdjdi hef GdfJGFL (B:(3GOJ GdYhdeI h XghQ GdYhdeI GdeYdheGJjI Gdi Ndb fhYjI LOjOI ef GdeHGfi GfJTQJ Ydi eSJhi GdYGde QZe GNJdGa GdGbGdje h GdXQha GdefGNjI gi GdeHGfi GdPcjI h GdJi JYO beI GdJbOe GdJcfhdhLi h GNQ eG JhUd Gdjg GdYde ai eLGd JcfhdhLjG GdeYdheGJ ai GdGdajg GdKGdKgs
(3GWQhMI (B((3OcJhQGI (B) - (3LGeYI MdhGf(B. (3cdjI Gdafhf GdJWHjbjI(B. (3bSe GdJUeje GdOGNdi h GdGKGK(B.s
(3JTJed Ydi EQLGYGJ HHdjhLQGajI (B((3U(B. 378-384 )s
(3GdfU HGddZI GdYQHjI(B, (3GdedNU HGddZI GdYQHjI hGdEfLdjRjI(B.s
Keywords: (3GdYeGQIs -- (3GdWQb GdafjIs -- (3HQGeL MGSHGJs